2021
DOI: 10.1038/s41401-021-00726-0
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin has therapeutic efficacy in colitis regulating gut microbiota, inflammation, and oxidative stress via the circ-Sirt1/Sirt1 axis

Abstract: Diosmetin (3',5,7 -trihydroxy-4'-methoxy flavone) is a natural flavonoid compound in the citrus species, it exhibits a variety of pharmacological activities, but little is known of its effects on colitis. In this study we evaluated the therapeutic effects of diosmetin on mouse models of chronic and acute colitis. Chronic colitis was induced in mice by drinking water containing 3% dextran sulfate sodium (DSS) from D0 to D8, followed by administration of diosmetin (25, 50 mg • kg −1 • d −1 ) for another 8 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…ZO-1 ( Furuse et al, 1994 ), occludin ( Furuse et al, 1998 ), and claudin-1 are intestinal epithelial barrier proteins, which are very important for the stability of epithelial barrier function. Previous studies have shown that geniposide and diosmetin can improve colitis by significantly increasing the damaged intestinal barrier protein ( Xu et al, 2017 ; Li et al, 2021b ). In the experiment, we found that the expression of related barrier proteins ZO-1, occludin, and claudin-1 increased significantly after silencing the transcription factor CEBPB.…”
Section: Discussionmentioning
confidence: 99%
“…ZO-1 ( Furuse et al, 1994 ), occludin ( Furuse et al, 1998 ), and claudin-1 are intestinal epithelial barrier proteins, which are very important for the stability of epithelial barrier function. Previous studies have shown that geniposide and diosmetin can improve colitis by significantly increasing the damaged intestinal barrier protein ( Xu et al, 2017 ; Li et al, 2021b ). In the experiment, we found that the expression of related barrier proteins ZO-1, occludin, and claudin-1 increased significantly after silencing the transcription factor CEBPB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Diosmetin is cytotoxic to BRCA cells ( Androutsopoulos et al, 2009 ). Based on its anti-inflammatory and antiviral effects ( Lee D. H. et al, 2020 ; Li et al, 2022 ), we hypothesized that Diosmetin might have an effective pharmacological activity on patients with BRCA/COVID-19. In the previous analysis, we identified 337 core genes that were associated with the development of COVID-19 and were also involved in the development of breast cancer, among which 219 were upregulated and 119 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Chryseriol is a flavonoid with various biological properties such as antioxidant, anti-inflammatory, and immunomodulatory effects, exerting antioxidant and anti-inflammatory effects by inhibiting Nrf2 and NF-κB signaling pathways, respectively [29,30]. Diosmetin has both anti-inflammatory and antioxidant effects and has been shown to significantly inhibit the activation of inflammatory factors and to downregulate reactive oxygen species levels [31,32]. Alisol B 23acetate can downregulate inflammatory mediators by inhibiting NF-κB and MAPK signaling pathways [33].…”
Section: Discussionmentioning
confidence: 99%